Efektifitas Kompres Dingin dan Teknik Relaksasi Nafas Dalam untuk Skala Nyeri Pasien Saat Kanulasi (Inlet Akses Femoral) di Unit Hemodialisa RSUD Cilacap - Pranowo, Suko; Iskandar Afifi, Ahmad (Jurnal Kesehatan Al-Irsyad, 2021)
Hemodialysis cannulation action will respond to discomfort due to stimulation of a large needle puncture. The puncture stimulates sensory nerve fibers which cause pain. This study aims to determine the differences in the effectiveness of cold compresses and deep breath relaxation techniques to reduce patient pain during hemodialysis cannulation (femoral access inlet) in the Hemodialysis Unit of the Cilacap Hospital. This type of research is a quasy experimental study with a static group comparison design of 12 people who received cold compresses and 12 people who received deep breath relaxation techniques that were taken using the total sampling method. Data analysis using t-test. The results showed that there was a significant difference in the pain scale of patients during cannulation (inlet femoral access) hemodialysis before and after being given cold compresses (pv = 0.001, α = 0.05), there was a significant difference in the pain scale of patient during cannulation (inlet femoral access) hemodialysis before and after being a deep breathing relactation technique (pv = 0.002, α = 0.05), there was no significant difference between the patient’s pain scale during cannulation (femoral access inlet) hemodialysis after being given cold compresses and after being given deep breathing relaxation techniques (pv = 0,081, a = 0,05).